2010
DOI: 10.1212/wnl.0b013e3181ebdd3e
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity and language impairment in cryptogenic localization-related epilepsy

Abstract: Impaired performance on language assessment in epilepsy patients is associated with loss of functional connectivity in the cognitive language networks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 44 publications
4
61
4
Order By: Relevance
“…We are aware of one other study using a verbal fluency paradigm to study task‐based connectivity in TLE 10. These authors concluded that, “impaired language function may not necessarily be reflected by altered patterns or levels of cerebral activation, but may be characterized by improperly orchestrated activity in the language network” 10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are aware of one other study using a verbal fluency paradigm to study task‐based connectivity in TLE 10. These authors concluded that, “impaired language function may not necessarily be reflected by altered patterns or levels of cerebral activation, but may be characterized by improperly orchestrated activity in the language network” 10.…”
Section: Discussionmentioning
confidence: 99%
“…While structural “network disease” is unlikely to explain cognitive impairment in all cases,9 the underlying concept can be expanded to incorporate functional network disease as well. From this perspective some of the cognitive deficits in TLE, and indeed in epilepsy more generally, represent alterations in functional networks 9, 10, 11…”
Section: Introductionmentioning
confidence: 99%
“…Bettus et al (2009) found decreased basal functional connectivity in the left hemisphere in patients with LTLE, and in addition, they also observed increased basal functional connectivity within the right hemisphere in the same patient group. Cognitive impairments in patients with TLE have also been correlated with changes in functional connectivity (Vlooswijk et al, 2010;Waites et al, 2006;Zhang et al, 2009). Liao et al (2010) found both increases and decreases in resting-state functional connectivity in patients with TLE; two regions with significant decreases in connectivity displayed a negative correlation with the duration of epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4]6 Graph-theory analysis of resting-state fMRI data from patients with epilepsy also revealed decreased functional nodal topologic properties of the DMN that were positively correlated with disease duration. 8,[11][12][13][14] Regional homogeneity analysis of resting-state fMRI data was even used as a presurgical tool for seizure identification in patients with MR-negative focal epilepsy. 15 Thus, various models of data analysis have helped in understanding epilepsy further, and now there is increasing interest in using these models to reclassify epilepsy as a focal epileptogenic area 10,15 or as a network of seizure-generating areas.…”
mentioning
confidence: 99%